Michael Armitage : Paradise Edict - Schneider, Anna; Stöckle, Dimona; Handa, Don; Coovadia, Imraan; Court, Elsbeth Joyce; Royal Academy of Arts, London (Köln : Verlag der Buchhandlung Walther und Franz König, 2020)
Gichugu, Meek ; Katarikawe, Jak ; Lilanga, George ; Ng'ethe Macua, Asaph ; Mulindwa, Peter ; Musoke, Theresa ; Njau, Elimo ; Odundo, Magdalene ; van Rampelberg, Chelenge ; Saidi Tingatinga, Edward ; Wadu, Sane
Paradise Edict, Haus der Kunst, Munich, 4 September 2020 - 14 February 2021. - Royal Academy of Arts, London, 13 March 2021 - 6 June 2021
boek
Keywords: Armitage, Michael